Individuals with clinically significant insomnia symptoms are characterised by a negative sleep-related expectancy bias: Results from a cognitive-experimental assessment. (August 2017) - Courtauld, Hannah; Notebaert, Lies; Milkins, Bronwyn; Kyle, Simon D.; Clarke, Patrick J.F.
Abstract: Cognitive models of insomnia consistently suggest that negative expectations regarding the consequences of poor sleep contribute to the maintenance of insomnia. To date, however, no research has sought to determine whether insomnia is indeed characterised by such a negative sleep-related expectancy bias, using objective cognitive assessment tasks which are more immune to response biases than questionnaire assessments. Therefore, the current study employed a reaction-time task assessing biased expectations among a group with clinically significant insomnia symptoms (n = 30) and a low insomnia symptoms group (n = 40). The task involved the presentation of scenarios describing the consequences of poor sleep, and non-sleep related activities, which could be resolved in a benign or a negative manner. The results demonstrated that the high insomnia symptoms group were disproportionately fast to resolve sleep-related scenarios in line with negative outcomes, as compared to benign outcomes, relative to the low insomnia symptoms group. The two groups did not differ in their pattern of resolving non-sleep related scenarios. This pattern of findings is entirely consistent with a sleep-specific expectancy bias operating in individuals with clinically significant insomnia symptoms, and highlights the potential of cognitive-experimental assessment tasks to objectively index patterns of biased cognition in insomnia. Highlights: Insomnia is thought to be underpinned by a sleep-specific negative expectancy bias. This has not yet been assessed with an objective measure. A cognitive-experimental assessment is used to assess expectancy bias in insomnia. The high insomnia symptoms group showed a sleep-specific negative expectancy bias. Confirms the presence of sleep-specific biased expectations operating in insomnia.